Phytochemicals Screening in Four Solvent Extractions of Pulverized Witchweed (Striga asiatica) - G. F. Kontagora; N. M. Ibrahim (Journal of Applied Sciences and Environmental Management)
Striga asiatica, commonly known as Witchweed, is a parasitic plant that significantly impacts cereal crops such as maize, sorghum, and millet, leading to severe agricultural losses. Besides its agricultural threat, S. asiatica has a rich history of use in traditional medicine for treating various ailments. This research focuses on analyzing the phytochemical composition of S. asiatica using four different solvent extracts: ethyl acetate, methanol, chloroform, and N-hexane from pulverized plant material. The goal is to identify the primary bioactive constituents and explore their potential medicinal properties. Standard analytical techniques were employed to evaluate the phytochemical profiles of the different solvent extracts. The study consistently identified alkaloids, cardiac glycosides, and triterpenes across all extracts. Flavonoids, saponins, and tannins were specifically present in the ethyl acetate and methanol extracts but were absent in chloroform and N-hexane extracts. Notably, anthraquinones and steroids were not detected in any of the solvent extracts, suggesting a unique phytochemical profile for S. asiatica. An important finding is the significant activity of the N-hexane extract against pathogenic organisms such as Culex quinquefasciatusaa, indicating potential antifungal and antihelminthic properties. These results underscore the diverse phytochemical profile of S. asiatica and its potential therapeutic applications. The study highlights the need for further research to fully understand the bioactive compounds and their mechanisms of action, which could lead to new applications in medicine and agriculture.